The influence of Motivation, Competency and Working Facilities on Employee Performance at PT Pertamina MOR IV Semarang - Tirta - Sandy; Winarto - Winarto; Subandi - Subandi (JOBS (Jurnal Of Business Studies), 2020)
The purposed of this research to analyze employee performance, especially in the office of Pertamina MOR IV Semarang. This research used variables work motivation, work competence, and work facilities as independent variables that affect employee performance as the dependent variable. Sample used 102 employees of the office of Pertamina MOR IV Semarang and using the incidental sampling method, the study was using multiple regression analyze to. The results showed that work motivation, work competence, and work facilities had influences toward employee work performance. Motivation variable has Coefficient regression value of 0.285, competency is 0.238, and working facility is 0.273. Among the three independent variables, motivation has the largest effect on employee performance at PT. Pertamina MOR IV Semarang